AI-Driven Automation for Analog and Mixed-Signal Circuit Design: Schematic to GDSII Layout - Sri Sockalingam, Jiveya; Chiew Wong, Yan; Sarban Singh, Ranjit Singh; Anand, T. Joseph Sahaya (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2024)
As technology propels forward and circuits evolve into intricate and complex designs, the traditional manual circuit design approach finds itself at a crossroads. With cutting-edge processes introducing many challenges, the journey from concept to creation has become increasingly arduous, demanding significant time investments. To overcome these challenges, automation emerges as a key innovation, accelerating product development while ensuring precision. This study explores analog circuit design by investigating the architecture of an analog and digital circuit generator and pioneering an automated synthesis method called “correct-by-construction”. This innovative approach optimizes the design process while prioritizing accuracy from the outset. Additionally, this study evaluates the performance of analog generators, focusing on accuracy and circuit metrics using AutoCkt. Tools such as ALIGN for automated layout generation and OpenFASoC for digital design automation further enhance efficiency and accessibility in analog circuit design. The integration of these tools, alongside their compatibility with open-source CAD platforms, demonstrates significant advancements in automation. Furthermore, the development of a graphical user interface (GUI) provides a user-friendly platform for interacting with various functionalities related to circuit design and simulation, enhancing the overall design workflow.